Formation of the concept of holistic management of assets and value of organizations in conditions of economic instability - Glukhov Vladimir; Pupentsova Svetlana (π-Economy)
Under the pressure of sanctions, modern domestic management is going through a turbulent time: the rules of the game, the composition of market participants, and the scale of the playing field are changing. The new reality requires the realization that there is nothing permanent in the surrounding world, which forces to apply completely new approaches to corporate governance, information security, strengthening competitive positions and attracting investments. The elements of the concepts of value management and sustainable development of organizations, risk management and innovation management considered in the article are developing separately. But modern organizations need an integrated holistic approach to management that combines the above concepts. The analysis uses general scientific methods of comparative analysis of the main provisions, systematization of data and generalization of domestic and foreign experience of modern management concepts. The purpose of the study is to form the concept of holistic approach to the management of assets and value of organizations, ensuring sustainable development in the context of economic instability. The article presents the analysis of scientific publications in the field of concepts of value management of organizations, the concept of social responsibility and sustainable development, innovation and risk management. The authors have developed a system of principles and presented their own definition of holistic management of assets and value of organizations that ensures sustainable development in the context of economic instability. Future research on the development of methodological recommendations of the main provisions of the concept of holistic management of assets and value of organizations can be based on the results obtained in this study.